Intelligent Satellite Internet Maintenance and Management:Progress and Opportunities - Siqi TANG; Zhisong PAN; Guyu HU; Yang WU; Yunbo LI (天地一体化信息网络)
In multi-layer heterogeneous satellite internet, the time-varying topology, dynamic channel quality, unstable satellites and emerging high-dimensional data present daunting challenges to its maintenance and management system.Thanks to its ability to learn from massive historical data or interaction with dynamic environment, artificial intelligence has been considered to be a promising solution to meet the aforementioned challenge.In this paper, we reviewed the research status of intelligent satellite internet maintenance and management technology on the following three aspects, network resource management, traff c fl ow management and network state management.Based on the above introduction, we further discussed the limitation of existing research and discussed promising future research direction of this fi eld as well.